Multifaceted Alliances to Simbolically Reclaim Urban Space: The Case of Tor Pignattara in Rome - Antonia De Michele (lo Squaderno)
The paper focuses on the Tor Pignattara neighbourhood in Rome, describing a non-linear trajectory of transformation where demographic shifts have generated tensions and alliances between old and new residents. Located in the eastern periphery of Rome, Tor Pignattara is a territorially ambiguous area, shaped by unregulated urban expansion and characterized by hybridity in its urban landscape and social composition. Historically marked by a strong working-class identity from domestic post-war migrations, today it is one of Rome’s most multicultural districts, with significant immigrant communities from Bangladesh, China, India, and North Africa. In recent decades, the neighbourhood has faced social and urban transformations due to real estate pressure and gentrification, though distinct from the adjacent Pigneto area1. In Pigneto, transformation largely resulted from an economic-political strategy, involving substantial investments in urban regeneration and symbolic rebranding, exemplified by the“Pigneto Village”campaign(Scandurra,2007).Thisinstitutionalprocessredefinedthespaceinabstractterms, distorting its reality and aligning it with neoliberal urban marketing objectives, which have fostered socio-spatial inequalities.